Pembelajaran Tari Buchaechum Menggunakan Model Kooperatif di Kelas X SMK Madyatama Palembang - Novianti, Melsa; Nurdin, Nurdin; Kurniawan, Irfan (Indonesian Research Journal on Education, 2023)
The purpose of this study was to determine the teacher's efforts in improving student learningoutcomes in cultural arts subjects, especially Buchaechum Dance in class X SMK MadyatamaPalembang. This type of research uses descriptive qualitative research methods, namely bypresenting data and using a sentence in the form of text. The object of this research is the teacher of arts and culture, while the informants are students. Qualitative research method is a research process that begins with the rules of thinking and formulating basic assumptions that will be included in the research. The results of the study showed that the obstacles faced by teachers were the lack of interest in student learning and inadequate facilities and infrastructure to support success in learning activities. Then came the efforts made by a teacher at SMK Madyatama Palembang to improve student learning outcomes, namely the teacher changing the learning method, the method that theteacher uses is a varied method, namely the Demonstration method and the Peer Tutor method as well as the use of Audio Visual aids media